Asuhan Keperawatan Gerontik pada Lansia Dengan Pemberian Air Rebusan Daun Salam Terhadap Penurunan Kadar Asam Urat dan Intensitas Nyeri Arthitis Gout pada Lansia di Panti Pelayanan Sosial Lanjut Usia Dewanata Cilacap - Alfian Indriyanto; Prasanti Adriani (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Elderly is an age group that is susceptible to disease due to decreased function in the body due to the aging process. Uric acid is produced by every living thing as a result of the main metabolic process, namely a chemical process in the cell nucleus that functions to support survival. To overcome complaints of pain that appear in patients with gout, there are various pharmacological and non-pharmacological therapies. The usual pharmacological therapy is taking painkillers, namely the Nonstereoidal Antiinflammatory Drugs (NSAID) group. Complementary therapy is a natural therapy including herbal therapy in the form of bay leaves. The aim of the study was to describe a decrease in uric acid levels by giving bay leaf boiled water to the elderly at the Cilacap Dewanata Institution. The results of this study were obtained after therapy by giving boiled bay leaf water, the patient was more comfortable, the pain was reduced, the last day's observations of vital signs (TTV) showed Td: 110/80 mmHg, Respiration: 20 x/minute, Pulse: 96 x /minute pain scale 2. In conclusion, the application of giving bay leaf boiled water is proven to be able to overcome the problem of diagnosing acute pain associated with physical injury agents, the implementation of self-invasion care was carried out for 3 days, with extraction the results of reduced pain.